2020
DOI: 10.2217/bmm-2020-0205
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Markers of Erythropoietin Deficiency Anemia in Chronic Kidney Disease (Predialysis) Patients

Abstract: Aim: To determine the clinical and genetic markers associated with erythropoietin deficiency anemia in predialysis individuals. Materials & methods: Patients were categorized into cases and control group. Demographic characteristics and clinical parameters were obtained from medical record review and serum EPO and ferritin were obtained with ELISA. HIF-1α (rs2057482), IL-1β (rs1143627) and EPO (rs1617640) gene polymorphism were genotyped. Results: Female gender, glomerular filtration rate, treatment with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…Interestingly, the top common SNP of our study (rs9402685) and the associated HBS1L-MYB locus showed a robust association with Epo levels ( P =1.46 x10 -4 ), confirming the previously published results. 4 The SNP rs1617640 of the EPO locus itself has been reported to be associated with low Epo serum levels in predialysis chronic kidney disease patients, 9 but neither this SNP nor any other SNP of the EPO locus (lowest P =0.17 at rs7789679) were associated with Epo levels in our study.…”
contrasting
confidence: 64%
“…Interestingly, the top common SNP of our study (rs9402685) and the associated HBS1L-MYB locus showed a robust association with Epo levels ( P =1.46 x10 -4 ), confirming the previously published results. 4 The SNP rs1617640 of the EPO locus itself has been reported to be associated with low Epo serum levels in predialysis chronic kidney disease patients, 9 but neither this SNP nor any other SNP of the EPO locus (lowest P =0.17 at rs7789679) were associated with Epo levels in our study.…”
contrasting
confidence: 64%
“…Nephropathy is generally a progressive disease, which is associated with endocrine failure (erythropoietin and 1,25-dihydroxycholecalciferol) with attendant systemic effects that resemble accelerated aging. 56,57 Inadequate secretion of erythropoietin by the kidney in response to low hemoglobin drive aggravates chronic hemolytic anemia of SCD and might even result in transfusion dependence. Uremia also reduces erythrocyte survival by damaging red cell membrane, making them prone to phagocytosis by the macrophages in the reticuloendothelial system.…”
Section: Renal Morphological and Functional Changes In Scd Can Be Bot...mentioning
confidence: 99%
“…58 There could also be nutritional anemia from malnutrition and dialysis-related nutrients deficiency, in addition to increased hepcidin that interferes with intestinal absorption of iron. 57 The other important endocrine dysfunction associated with the nephropathy is abnormal vitamin D metabolism. Calcium absorption from the gastrointestinal tract is regulated by an active vitamin D called 1,25-dihydroxycholecalciferol (calcitriol), which is produced by the kidney.…”
Section: Renal Morphological and Functional Changes In Scd Can Be Bot...mentioning
confidence: 99%